NG2/CSPG4 regulates cartilage degeneration during TMJ osteoarthritis - David A. Reed; Yan Zhao; Mina Bagheri Varzaneh; Jun Soo Shin; Jacob Rozynek; Michael Miloro; Michael Han (Frontiers Media S.A., 2022)
Changes in the mechanical homeostasis of the temporomandibular joint (TMJ) can lead to the initiation and progression of degenerative arthropathies such as osteoarthritis (OA). Cells sense and engage with their mechanical microenvironment through interactions with the extracellular matrix. In the mandibular condylar cartilage, the pericellular microenvironment is composed of type VI collagen. NG2/CSPG4 is a transmembrane proteoglycan that binds with type VI collagen and has been implicated in the cell stress response through mechanical loading-sensitive signaling networks including ERK 1/2. The objective of this study is to define the role of NG2/CSPG4 in the initiation and progression of TMJ OA and to determine if NG2/CSPG4 engages ERK 1/2 in a mechanical loading-dependent manner. In vivo, we induced TMJ OA in control and NG2/CSPG4 knockout mice using a surgical destabilization approach. In control mice, NG2/CSPG4 is depleted during the early stages of TMJ OA and NG2/CSPG4 knockout mice have more severe cartilage degeneration, elevated expression of key OA proteases, and suppression of OA matrix synthesis genes. In vitro, we characterized the transcriptome and protein from control and NG2/CSPG4 knockout cells and found significant dysregulation of the ERK 1/2 signaling axis. To characterize the mechanobiological response of NG2/CSPG4, we applied mechanical loads on cell-agarose-collagen scaffolds using a compression bioreactor and illustrated that NG2/CSPG4 knockout cells fail to mechanically activate ERK 1/2 and are associated with changes in the expression of the same key OA biomarkers measured in vivo. Together, these findings implicate NG2/CSPG4 in the mechanical homeostasis of TMJ cartilage and in the progression of degenerative arthropathies including OA.